(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
In the article, the linguistic lines of verbal appearance are examined as a basic mean of realization of aesthetically beautiful function of language. Basic attention is spared finding out of specific of linguistic mechanism of formation of tropes through unusual compatibility of words of, which provides actualization of artistic utterance.